The Protection of Performers’ Rights under the Copyright Act 2022: A Critique - Alabi, Stephen (ABUAD Law Journal, 2022)
The protection of Neighbouring Rights is an essential aspect of the legal regime of copyright in every jurisdiction. This is more so in Nigeria where there has been an explosion of the film industry, musical performances and radio and television broadcasting which these rights protect and an even greater explosion of technology with which rights protectable under copyright statutes can be infringed upon. The Nigerian Copyright Act Cap. C28 Laws of the Federation of Nigeria 2004 made copious provisions for the protection of Neighbouring Rights in Part II thereof. However, over time, these provisions became inadequateto secure the protectable interests of performers with the increase in open and sleuth technology and the tenacity of infringers to undermine the interests of rights owners. The agitation of stakeholders to review the statute to accommodate new challenges in the industry has yielded fruit with the signing into law of the new Nigerian Copyright Act 2022 by former President Muhammadu Buhari. This paper looks at the provisions of the new Act to ascertain how well they protect performers’ rights against the background of the challenges that led to a review of the old Act. The paper does a comparison of the new provisions with the old provisions and with provisions in similar jurisdictions outside Nigeria. The paper finds that the new Act has greatly improved the protection available to performers and adequately meets international standards.